A COMPREHENSIVE REVIEW OF PHARMACEUTICAL VALIDATION AND QUALIFICATION: CONCEPTS, PRACTICES, AND EVOLVING TRENDS - Meena, Manish; Jain, Anvesh; Panwar, Mangal S (Journal of Global Pharma Technology, 2025)
Pharmaceutical validation is a critical component of current Good Manufacturing Practices (cGMP), ensuring that processes, systems, and methods consistently produce products that meet predetermined quality standards. This review explores the principles and types of validation with a focus on process validation, equipment qualification, analytical method validation, cleaning validation, and computer system validation. Emphasis is placed on the regulatory frameworks provided by agencies such as the FDA and EMA, as well as the lifecycle approach to validation, which includes process design, qualification, and continued verification. The article also highlights recent advancements such as risk-based validation strategies, the use of automation and digital tools, and the implementation of ICH guidelines. By integrating both foundational knowledge and emerging trends, this review provides a strategic overview valuable for quality assurance professionals, regulatory personnel, and pharmaceutical researchers. Keywords: Pharmaceutical Validation, Process Qualification, cGMP, Risk-Based Validation, Lifecycle Approach.